(Application of Make A Match Learning Method (Looking for Couples) to Increase Learning Result of Science Knowledge at Class V SD Negeri 187 Pekanbaru): PENERAPAN METODE PEMBELAJARAN MAKE A MATCH (MENCARI PASANGAN) UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM PESERTA DIDIK KELAS V SD NEGERI 187 PEKANBARU - Nurani Nurani (UIR Press, 2018)
This research is based on the low level of science learning result obtained by class V students classically still under the determined mastery that is 75%. This study aims to determine the improvement of learning outcomes of class V students of State Elementary School 187 Pekanbaru through the application of learning methods Make A Match (Seeking Couples). This research is a classroom action research. The purpose of this study is to improve the learning outcomes of science class V students of State Elementary School 187 Pekanbaru using Learning Method Make A Match (Looking for Couples). The subjects of this study were students in class V State Elementary School 187 Pekanbaru which amounted to 22 students. Based on the results of the research it can be seen the increase in learning outcomes before the first cycle of action and cycle II. Before the students' learning outcomes were classified as